Analisis Cost Volume Profitabilitas Sebagai Alat Bantu Perencanaan Laba Dalam Mencapai Target Pada Toni Meubel Way Bungur - Wahyuni, Evi; Nusantoro, Jawoto; Darmayanti, Elmira Febri (Universitas Muhammadiyah Metro, 2023)
The purpose of this study is to be able to determine the contribution margin, the level of break event point sales, safety of margin and the number of goods sold at Toni Meubel Way Bungur to achieve a profit target and to know the level of operating leverage at Toni Meubel Way Bungur resulting in increased profits. clean. This research is a quantitative research which is a process of analyzing something you want to know by using data in the form of numbers as a supporting tool. The data collected is in the form of data on operational costs or variable costs, fixed costs, and furniture sales data at Toni Meubel in Way Bungur. Based on the description above, the results of the research and discussion can be concluded as follows. The contribution margin of Toni Furniture Way Bungur has decreased from 2019-2021. The sales point break event level at Tony Way Bungur is so that the company does not experience a loss of at least 10 units. Safety of margin at Toni Meubel Way Bungur has fluctuated from 2019-2021. The safety margin in 2020 has decreased, but in 2021 it has increased again. The number of items sold at Toni Meubel has fluctuated in 2019-2021.